Qualitative evaluation of the feasibility of a national whole-school program for reducing school violence and improving school climate in Chile - López, Verónica; Carrasco-Aguilar, Claudia; Jervis, Pamela; Torres-Vallejos, Javier; Ramírez, María Teresa; González, Juan Pablo Álvarez; Franulic, Amanda (Frontiers in Education, 2025)
IntroductionGlobally, school violence has increased since the return to in-person classes following the COVID-19 pandemic lockdown. Since then, this indicator has become critical, especially in Latin American countries. In this context, the Chilean Ministry of Education, with the support of 17 universities, began in 2022 the design and implementation of a comprehensive educational reactivation policy. This policy included a focus on school climate (convivencia escolar) and mental health through a nationwide intervention program now called the Learning to Live Together Program (Programa A Convivir se Aprende), designed using a whole-school approach.MethodsThis study presents the results of a large-scale qualitative evaluation of the initial feasibility of the program, framed in a mixed-methods design. The evaluation identified schools with high, intermediate, and low initial acceptability of the program through 66 interviews and focus groups with 215 participants, including school members, representatives from the Ministry of Education, and university advisors.ResultsThe reflexive thematic analysis identified four categories featuring six dimensions, 95 codes, and 3,040 textual quotes. The results show a positive acceptance of the program, with high adherence and commitment from the schools. The most highly valued aspects of the program were the conceptual model based on a whole-school approach, the possibility of working with universities in their territories, and school climate networks that were viewed as professional learning communities. Recommendations for future implementation of the program relate to longer implementation time, incorporating actions to promote mental health, expanding participation in the management of school climate, and greater presence of the ministry.DiscussionWe discuss these findings in relation to the program’s theory of change, suggesting that the program can achieve its goal of improving school staffs’ skills and competencies in managing school climate and reducing school violence, especially through the strategy of school climate networks by means of capacity building, shared reflexive processes, and emphasis on data-driven decision making.